The No Guidance Argument. (10th December 2012) - Steglich‐Petersen, Asbjørn
Abstract: In a recent article, I criticized Kathrin Glüer and Åsa Wikforss's so‐called "no guidance argument" against the truth norm for belief, for conflating the conditions under which that norm recommends belief with the psychological state one must be in to apply the norm. In response, Glüer and Wikforss have offered a new formulation of the no guidance argument, which makes it apparent that no such conflation is made. However, their new formulation of the argument presupposes a much too narrow understanding of what it takes for a norm to influence behaviour, and betrays a fundamental misunderstanding of the point of the truth norm. Once this is taken into account, it becomes clear that the no guidance argument fails.